2018
DOI: 10.1007/s00784-018-2519-6
|View full text |Cite
|
Sign up to set email alerts
|

Topical pimecrolimus versus betamethasone for oral lichen planus: a randomized clinical trial

Abstract: The study proved the benefits of topical pimecrolimus in early management of painful lesions of OLP and its ability to inhibit CSCs, suggesting a possible role in reducing risk of malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
1
24
0
1
Order By: Relevance
“…Regarding its efficacy, two randomized double‐blind, vehicle‐controlled studies concluded pimecrolimus 1% to be superior to vehicle in reducing pain, erythema, lesional size and overall severity in oral LP . Another randomized, controlled trial comparing pimecrolimus 1% with betamethasone 0.1% has shown that pimecrolimus 1% demonstrates earlier clinical response and less recurrence rate after 4 weeks of therapy . One prospective study concluded pimecrolimus 1% to be superior to topical triamcinolone acetonide 0.1% paste for oral LP …”
Section: Topical Calcineurin Inhibitorsmentioning
confidence: 99%
“…Regarding its efficacy, two randomized double‐blind, vehicle‐controlled studies concluded pimecrolimus 1% to be superior to vehicle in reducing pain, erythema, lesional size and overall severity in oral LP . Another randomized, controlled trial comparing pimecrolimus 1% with betamethasone 0.1% has shown that pimecrolimus 1% demonstrates earlier clinical response and less recurrence rate after 4 weeks of therapy . One prospective study concluded pimecrolimus 1% to be superior to topical triamcinolone acetonide 0.1% paste for oral LP …”
Section: Topical Calcineurin Inhibitorsmentioning
confidence: 99%
“…Vehicle 5 Betamethasone valerate 0.1% cream 6 Pimecrolimus was found to be more effective than vehicle, but less effective than betamethasone. Oral erosive lichen planus Vehicle [7][8][9][10] Triamcinolone acetonide 0.1% paste 11 Betamethasone valerate 0.1% cream 12 Tacrolimus 0.1% ointment 13,14 Pimecrolimus was found to be more effective than vehicle, and similarly effective as topical corticosteroids and tacrolimus. A smaller proportion of patients treated with pimecrolimus required retreatment.…”
Section: Intertriginous Psoriasismentioning
confidence: 97%
“…OLP is a T cell‐mediated chronic inflammatory disease targeting the basal keratinocytes . CD4 helper T cells are activated by an unknown antigen, which secrets cytokines and interleukins that recruit Langerhans and CD8 cytotoxic T cells .…”
mentioning
confidence: 99%
“…CD4 helper T cells are activated by an unknown antigen, which secrets cytokines and interleukins that recruit Langerhans and CD8 cytotoxic T cells . Cytotoxic T cells trigger apoptosis of the basal cells (target cells) …”
mentioning
confidence: 99%
See 1 more Smart Citation